Affect Of E-Service Quality On E-Customers Loyalty Through E-Customers Satisfaction On E-Commerce Shopee - Iranda Kayla Avania; Arry Widodo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The rapid development of the digital economy in Indonesia has had a positive impact on the national economy, one of which is the growth of various online trading platforms or e-commerce. This study aims to determine the effect of e-service quality on e-customers loyalty through e-customers satisfaction as an intervening variable. The method used in this research is quantitative with descriptive and causal research and SEM-PLS analysis method. The sampling technique used is a non-probability sampling technique, using the slovin formula with a sample of 100 respondents who have used the Shopee e-commerce application in Batam City. The results of the influence test using the structural model show that e-service quality has a positive but not significant effect on e-customers loyalty, then e-service quality has a positive and significant effect on e-customers satisfaction, then e-customers satisfaction has a positive and significant effect on e-customers customer loyalty. Tests using the intervening variable show that e-customers satisfaction mediates the effect of e-service quality on e-customers loyalty. This illustrates that the ups and downs of e-customers loyalty for the Shopee e-commerce application are determined by e-customers satisfaction, and the fluctuations in e-customers satisfaction for the Shopee e-commerce application are determined by several factors, including e-service quality.